"NOTA‐PRGD2 and NODAGA‐PRGD2: Bioconjugation, characterization, radiolabelling, and design space". (25th April 2018) - Salvé, Mallory; Avohou, Hermane T.; Monbaliu, Jean‐Christophe M.; Lebrun, Pierre; Lemaire, Christian; Damblon, Christian; de Tullio, Pascal; Hubert, Philippe; Hustinx, Roland; Luxen, André
Abstract : This work reports on the development of amide bond bioconjugation for the production of ‐NOTA and ‐NODAGA PRGD2 using batch strategy and microfluidic reactor technology. The final radiolabelling step was fully optimized using Design of Experiments and Design Space approaches, hence targeting robust labelling yields in routine. Optimal labelling conditions were defined in sodium acetate buffer as 168 μg/mL peptide concentration, 4.9 pH, 47.5°C temperature, and 12.5‐minute reaction time. Upon optimization, the Gallium‐68 radiolabelling was fully automated. All the work was designed to be compliant to the GMP environment and to support the pharmaceutical scale‐up.